2014
DOI: 10.3400/avd.oa.14-00077
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Specific Distributions of Isolated Soleal Vein Thrombosis and Risk Factors

Abstract: Objective:The relationship between specific distributions of isolated soleal vein thrombosis (SV T ) and risk factors was investigated. Subjects and Methods: The subjects included 93 patients with SV T diagnosed with ultrasonography. Results: In the acute thrombus distribution, the thrombi of central veins were significantly more frequent than the thrombi of medial veins in the unilateral SV T. The thrombi of central veins were not more significantly frequent than the thrombi of medial veins in the bilateral S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Recently, Ohgi S and Ohgi N investigated the characteristics of the isolated soleal vein thrombosis and its risk factors in 93 patients with symptomatic DVT in the soleal veins. 11 ) They demonstrated that: (1) the frequency of acute DVT was higher in the central and medial soleal veins than in other veins, (2) the isolated DVT in the central and medial soleal veins may result from the larger diameters of these veins compared with the others, as a local risk factor, and (3) in unilateral DVT cases, the frequency of DVT in the central soleal vein was higher than that in the medial soleal vein, and VVs may be involved as local factors. Our results concerning the site of IDDVT in patients with VVs ( Table 2 ) are in line with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ohgi S and Ohgi N investigated the characteristics of the isolated soleal vein thrombosis and its risk factors in 93 patients with symptomatic DVT in the soleal veins. 11 ) They demonstrated that: (1) the frequency of acute DVT was higher in the central and medial soleal veins than in other veins, (2) the isolated DVT in the central and medial soleal veins may result from the larger diameters of these veins compared with the others, as a local risk factor, and (3) in unilateral DVT cases, the frequency of DVT in the central soleal vein was higher than that in the medial soleal vein, and VVs may be involved as local factors. Our results concerning the site of IDDVT in patients with VVs ( Table 2 ) are in line with these results.…”
Section: Discussionmentioning
confidence: 99%
“…26,27) It would be beneficial to evaluate the properties and analyze the characteristics of the thrombosis for predicting the risk of recurrence by US. 28) ACCP evidence-based clinical practice guideline recommended that additional other test was not performed when the thrombus was observed (regardless proximal or distal veins) or not by US. 29) Ultrasonography was performed in 87.7% and venography was performed in 2.8% of patients in a survey by Japanese Society of Phlebology in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Ohgi and Ohgi [30] investigated the relationships between specific distributions of isolated thrombosis of the soleus vein sole thrombosis (SVT) and risk factors; in the vein classification, the soleus muscle was divided into six circulatory regions and intramuscular veins were divided into six groups-proximal, lateral, central, medial, distal medial, and distal lateral veins-based on the circulatory regions and deep veins communicated with intramuscular veins in these regions. Despite the similar approach, these authors did not, however, describe any morphometric data or the topography and distribution of the extramuscular soleus veins.…”
Section: Discussionmentioning
confidence: 99%